1996
DOI: 10.1074/jbc.271.17.10029
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Binding to Na+/Glucose Cotransporters Is Determined by the Carboxyl-terminal Half of the Protein

Abstract: D-Glucose is absorbed across the proximal tubule of the kidney by two Na ؉ /glucose cotransporters (SGLT1 and SGLT2). The low affinity SGLT2 is expressed in the S1 and S2 segments, has a Na ؉ :glucose coupling ratio of 1, a K 0.5 for sugar of ϳ2 mM, and a K 0.5 for Na ؉ of ϳ1 mM. The high affinity SGLT1, found in the S3 segment, has a coupling ratio of 2, and K 0.5 for sugar and Na ؉ of ϳ0.2 and 5 mM, respectively. We have constructed a chimeric protein consisting of amino acids 1-380 of porcine SGLT2 and amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…Therefore, we hypothesized that this region in subdomain II either lies close to the sugar-binding site, which appears only in the presence of Na ϩ , or represents part of the initial binding pocket (vestibule), which subsequently transfers glucose to the translocation pathway. Several groups have proposed that the glucose translocation region lies between helices 10 -13 of SGLT1, however, with low affinity to D-glucose and lost sensitivity to phlorizin (10,13). In this study, we suggest that the residues between aa 339 and 356 located between helix 8 and 9 also contribute to efficient high affinity D-glucose transport.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Therefore, we hypothesized that this region in subdomain II either lies close to the sugar-binding site, which appears only in the presence of Na ϩ , or represents part of the initial binding pocket (vestibule), which subsequently transfers glucose to the translocation pathway. Several groups have proposed that the glucose translocation region lies between helices 10 -13 of SGLT1, however, with low affinity to D-glucose and lost sensitivity to phlorizin (10,13). In this study, we suggest that the residues between aa 339 and 356 located between helix 8 and 9 also contribute to efficient high affinity D-glucose transport.…”
Section: Discussionmentioning
confidence: 58%
“…Many researchers have attempted to localize a substrate translocation pathway in SGLT1. Studies on chimera proteins of SGLT1/SGLT2 and a truncated protein (residues 407-648) showed that residues from 381-662 of SGLT1 are important for sugar transport, however, with less sugar specificity and lower sensitivity to the competitive inhibitor phlorizin (10,13). Also residues 457, 468, and 499 have been shown to play an important role in controlling the sugar binding of SGLT1 (14,15).…”
mentioning
confidence: 99%
“…If transferred to the brush border membrane at all, then the protein predicted by this mutation would have only the seven N-terminally located transmembranous domains, whereas domains 8 to 14 would be missing. Such a mutation has been shown to result in a nonfunctional glucose transporter because it lacks the transmembranous domains 10 to 13 that have been demonstrated to be essential for sugar binding and sugar translocation (15,19,20). It is interesting, however, that one patient (patient 06-1) homozygous for a truncating mutation showed a considerably lower glucose excretion, suggesting some glucose reabsorption by an unknown alternative mechanism.…”
Section: Discussionmentioning
confidence: 74%
“…A set of glycosylation mutants has yielded information on topology, and a chimera of the high affinity and low affinity isoforms has suggested that sugar binding is determined by the C-terminal half of the protein (8). From comparisons of SGLT1 homologues cloned from different species, certain residues have been hypothesized to be important in determining the kinetic differences between these isoforms (9).…”
mentioning
confidence: 99%